Mass development of a filamentous and likely nitrophilous aerophytic green alga on tree bark: Apatococcus ammoniophilus sp. nov. (Chlorophyta, Trebouxiophyceae) - Søchting, Ulrik; Friedl, Thomas; Moestrup, Øjvind; Grewe, Felix; Sun, Yukun; Çakır, Yağmur Tarhana; Ganzera, Markus; Glaser, Karin; Heesch, Svenja; Hammerle, Fabian; Nimptsch, Daniel; Olberg, Birgit; et al. (Frontiers in Microbiology, 2025)
IntroductionA filamentous green alga forming significant biomass on twigs and needles was observed to have increased invasively in Denmark in recent decades. It was particularly abundant in coniferous plantations in western parts of Denmark that experience the highest modelled concentration of atmospheric nitrogen deposition. However, its species identity and taxonomy remained unknown.Material and methodsSelected algal samples from various substrates were analyzed for their ribosomal DNA sequences, metagenomic, and biochemical compounds [polyols and mycosporine-like amino acids (MAAs)].ResultsPhylogenetic analyses revealed the alga’s position within the Trebouxiophyceae (Chlorophyta), forming an independent lineage within Apatococcus. Though it was associated with various other Trebouxiophyceae species, the metagenome showed exceptionally high coverage of the Apatococcus contigs, proving its predominance, consistent with the amplicon-based approach. The low molecular weight carbohydrates, arabitol, erythritol, and trehalose – with erythritol displaying the highest concentrations—were recovered. The presence of erythritol provided chemotaxonomic support for the classification in Apatococcus. Additionally, a unique UV-absorbing mycosporine amino acid (MAA), likely new for the Trebouxiophyceae, was found. The species is described here as A. ammoniophilus, and the observed morphological features leave no doubt that it has been recorded from Denmark more than a 100 years ago. Morphological features are shared with its closer relatives, such as the presence of a ring of particles surrounding the nucleus and the formation of two-celled units.DiscussionThe presence of low molecular weight carbohydrates and the unique MAA in A. ammoniophilus well explain the biochemical basis for its aeroterrestrial lifestyle, as these organic compounds protect against desiccation and UV-radiation, respectively. Even though the genotype of A. ammoniophilus has also been found in inconspicuous biofilms devoid of filamentous stages on various substrates with presumably low ammonia deposition, the very invasive colonization in recent decades in western Denmark is assumed to be due to ammonia deposition. Consequently, A. ammoniophilus is suggested to be a potential biological indicator of air borne nitrogen deposition. A possible connection between filamentous growth and nitrogen accumulation needs further investigation, including culture experiments.